Fourteen weeks of multicomponent training associated with flexibility training modifies postural alignment, joint range of motion and modulates blood pressure in physically inactive older women: a randomized clinical trial - Sobrinho, Andressa C. S.; Benjamim, Cicero Jonas R.; Luciano de Almeida, Mariana; Rodrigues, Guilherme da Silva; Feitosa Lopes, Laryssa Grazielle; Ribeiro de Lima, João Gabriel; Bueno Júnior, Carlos Roberto (Frontiers in Physiology, 2023)
Background: Body relaxation and pain reduction are some of the reported benefits of flexibility training (through active stretching exercises), however their effects on posture and blood circulation are uncertain. We aimed to investigate the effects of flexibility training (through active stretching exercises) in combination with multicomponent training (MT) on blood pressure (BP), and the correlation with changes in body alignment and flexibility in physically inactive women. Methods: Women aged 60 to 70 years were into three groups: multicomponent training group (MT), multicomponent training plus flexibility training group (FT), and control group (CG). After randomization, the resting blood pressure was measured and the participants were reallocated into subgroups according to pressure values > 130/80 mmHg (This classification is according to the American Heart Association (AHA), resulting in the subgroups: flexibility training (FT); flexibility training for hypertensive patients (FTSAH); multicomponent training (MT); multicomponent training for hypertensive patients (MTSAH); control group (CG); control group of hypertensive patients (CGSAH). The interventions lasted 14 weeks. Systolic (sBP) and diastolic (dBP) BP, range of motion (flexion and extension), and postural analysis by asymmetry in the frontal plane and asymmetry in the sagittal plane, displacement and the flexibility test were collected before (Pre) and after training (Post).